Objective measurement of nine gaze-directions using an eye-tracking device - Yo Iwata; Tomoya Handa; Hitoshi Ishikawa (Bern Open Publishing, 2020)
Purpose: To investigate the usefulness and efficacy of a novel eye-tracking device that can objectively measure nine gaze-directions. Methods: We measured each of the nine gaze-directions subjectively, using a conventional Hess screen test, and objectively, using the nine gaze-direction measuring device, and de-termined the correlation, addition error, and proportional error. We obtained two consecu-tive measurements of the nine gaze-directions using the newly developed device in healthy young people with exophoria and investigated the reproducibility of the measurements. We further measured the nine gaze-directions using a Hess screen test and the newly developed device in three subjects with cover test-based strabismus and compared the results. Results: We observed that the objective measurements obtained with the newly developed gaze-direction measuring device had significant correlation and addition error compared to the conventional subjective method, and we found no proportional error. These measure-ments had good reproducibility. Conclusion: The novel device can be used to observe delayed eye movement associated with limited eye movement in the affected eye, as well as the associated excessive movement of the healthy eye in patients with strabismus, similar to the Hess screen test. This is a useful device that can provide objective measurements of nine gaze-directions.